Manufacturing method of coal cake, manufacturing method of metallurgical coke, and strength improving material for coal cake
Patent Information
- Application Number
- JP2024566191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-07-14
- Filing Date
- 2024-05-29
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2044-05-29
AI Technical Summary
【0017】 本発明によれば、粘結性のバインダーを用いることなく、石炭ケーキの強度を向上させることができる石炭ケーキの製造方法を提供することができる。また、本発明によれば、石炭水分を低位に保ちながら、操業上十分な強度を有する石炭ケーキを製造することもできる。
Smart Images

Figure 0007652348000001 
Figure 0007652348000002 
Figure 0007652348000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a coal cake, a method for producing a metallurgical coke, and a method for producing a strength improving material for a coal cake. [Background technology]
[0002] Currently, in the production of pig iron using a blast furnace, coke produced by carbonizing coal in a coke oven is used as a reducing agent for iron ore and to ensure gas permeability inside the blast furnace. It is known that high-strength coke is preferable for efficient operation of the blast furnace. This is because if coke is powdered in the blast furnace, the resulting powder will deteriorate the gas permeability of the blast furnace, making it impossible to operate the blast furnace efficiently.
[0003] It is known that increasing the bulk density of the coal charged into the coke oven is an effective way to produce high-strength coke, and for this purpose, stamp-charge coke ovens are used. In the typical coke ovens currently used in Japan (hereinafter referred to as "top-charge coke ovens"), the coal, which is the raw material for coke, is charged by gravity from the top of the coke oven carbonization chamber, and the bulk density of the gravity-charged coal is 700-800 kg-dry / m 3 It is.
[0004] On the other hand, in the stamp charge type coke oven, the coal is compacted by a stamping device arranged on the side of the carbonization chamber of the coke oven before being charged into the coke oven, and the bulk density is 1000 kg-dry / m 3 After being processed into the above coal cakes, they are mechanically charged into the coke oven chamber from the side. By using a stamp charge coke oven, the density of the coke raw material can be increased before carbonization as described above, and higher strength coke can be produced than when produced in a top charge coke oven.
[0005] As mentioned above, stamp-charge coke ovens are superior to top-charge coke ovens in terms of coke strength, but if the strength of the coal cake produced by stamping is low, it may cause operational troubles such as the coal cake collapsing while being charged into the coke oven carbonization chamber. Therefore, technology to produce high-strength coal cakes is required for stable operation of stamp-charge coke ovens.
[0006] It is also known that the strength of the coal cake is greatly affected by the moisture content of the coal, and in stamp charge coke ovens, the moisture content of the coal is generally adjusted to 10 to 12 mass%. However, if the moisture content of the coal cake is high, the carbonization time increases accordingly, and the productivity decreases. Therefore, in order to improve the productivity of stamp charge coke ovens, there is a demand for technological development that can manufacture coal cakes with sufficient strength for operation while maintaining a low coal moisture content.
[0007] To date, the use of caking binders has been considered for the above-mentioned purpose. For example, Patent Document 1 reports a method in which caking coal is heated to 300 to 500°C and the coal in a softened and molten state is used as a binder for the coal cake. In addition, Non-Patent Document 1 reports that by adding pitch with a softening point of 80°C as a binder to the raw material, the strength of the coal cake is increased, and a coal cake with sufficient strength can be produced even under conditions where the coal moisture content is lower than usual. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 7-109467 [Non-patent literature]
[0009] [Non-Patent Document 1] SH Krishnan, et al., "Application of Binder in Stamp Charge Coke Making", ISIJ International, 44(2004), 1150. Summary of the Invention [Problem to be solved by the invention]
[0010] In the method using a caking binder described in Patent Document 1 and Non-Patent Document 1, the caking raw material adheres to the belt conveyor and stamping device during the process of transporting the coke raw material containing the caking binder and during the process of compacting the raw material with a stamping device. Therefore, the device needs to be cleaned frequently, resulting in a problem of reduced productivity.
[0011] An object of the present invention is to provide a method for producing a coal cake that can improve the strength of the coal cake without using a caking binder. [Means for solving the problem]
[0012] The inventors have conducted intensive research to solve the above problems, and have obtained experimental results showing that the strength of coal cake is improved by mixing synthetic fibers such as polyethylene with the raw materials of the coal cake. The inventors have also found that fibers can be used as binders for stamp-charge coke ovens, and that the length of the fibers has a significant effect on the strength of the coal cake. Furthermore, the inventors have revealed that the same effect can be obtained by using plant materials having a fibrous shape in response to the recent social demand for carbon neutrality, and have completed the present invention.
[0013] That is, the gist and configuration of the present invention are as follows. [1] A method for producing coal cake in a stamp charge coke oven, comprising the steps of: A method for producing coal cake, comprising the steps of: mixing a powdered coal cake raw material with fibers having a length of 1.0 mm or more and 200 mm or less and a length to diameter ratio of 10 or more; and stamping the resulting fiber mixture raw material to obtain a coal cake.
[0014] [2] The method for producing a coal cake described in [1] above, wherein the blending ratio of the fibers is 2.0 mass% or less relative to 100 mass% of the raw materials of the coal cake.
[0015] [3] A method for producing metallurgical coke, comprising carbonizing a coal cake produced by the method according to [1] or [2] above in a coke oven to obtain coke.
[0016] [4] A strength improving material for coal cake used in stamp charge coke ovens, characterized in that the fiber has a length of 1.0 mm or more and 200 mm or less. Effect of the Invention
[0017] According to the present invention, it is possible to provide a method for producing a coal cake that can improve the strength of the coal cake without using a caking binder. Also, according to the present invention, it is possible to produce a coal cake that has sufficient strength for operation while keeping the coal moisture at a low level. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention relates to a method for producing a coal cake in a stamp charge coke oven, and is characterized in that the method comprises mixing a powdered coal cake raw material with fibers having a length of 1.0 mm to 200 mm and a length to diameter ratio of 10 or more, and stamping the resulting fiber mixed raw material to obtain a coal cake.
[0019] First, fibers having a length of 1.0 mm or more and 200 mm or less and a ratio of length to diameter of 10 or more are blended and mixed with the coal cake raw material to obtain a fiber mixed raw material.
[0020] [Ingredients for coal cake] As the raw material for the coal cake, a powdered blended coal consisting mainly of raw coal generally used for coke production may be used. In addition to raw coal, non- or slightly caking coal, biomass, charcoal obtained by heating biomass, and other raw materials mainly composed of carbon may be used as long as the quality of the coke obtained by carbonizing the coal cake is not an issue.
[0021] The above raw material may be crushed using a hammer crusher or the like to a particle size of -3 mm (70 to 100 mass % of the raw material is crushed so that the proportion of particles with a particle size of 3 mm or less is 70 to 100 mass %) as is conventionally done in the operation of stamp charge coke ovens, and used as the raw material for the coal cake.
[0022] The moisture content of the coal cake raw material can be adjusted before and after the above-mentioned crushing treatment by drying using a coal moisture adjustment facility, spraying water from a nozzle, etc. The target value of the moisture content of the coal cake raw material is preferably 10 to 12 mass% for the purpose of increasing the strength of the coal cake, but for the purpose of improving productivity, the moisture content may be reduced within a range in which the strength of the coal cake does not become an issue.
[0023] [fiber] As the fibers, synthetic fibers such as nylon and polyester, natural fibers such as silk and cotton cut to any length, and plant materials having a fibrous shape may be used. A specific example of a plant material having a fibrous shape is fiber (EFB fiber) made by mechanically loosening empty fruit bunches (EFB) of palm trees.
[0024] In recent years, in response to the societal demand for reducing CO2 emissions, palm oil and palm kernel shells derived from oil palms are increasingly being used as fuels for biomass power generation, replacing traditional fossil fuels. On the other hand, palm bunches, which are the residue left after harvesting the fruit from oil palms, contain a lot of water and ash and are prone to decay, so most of them are currently discarded. Palm bunches have a fibrous shape, and by mechanically loosening them, fibers with a diameter of about 0.5 to 1.0 mm and a length of about 50 to 100 mm can be obtained.
[0025] In this way, if we can focus on the shapes of plants that are currently discarded and use them as binders for stamp-charge coke ovens, it will lead to effective use of resources. Also, materials other than those mentioned above can be used as binders for stamp-charge coke ovens as long as they are fibers that are mainly composed of carbon, oxygen, and hydrogen.
[0026] In the present invention, fibers having a certain length or more are mixed and dispersed in the raw material of the coal cake to form a network in which the fibers are intertwined with each other to produce a fiber mixed raw material, which allows the production of a coal cake with high strength.
[0027] The longer the fibers are, the more the fibers come into contact with each other, and a fiber network is formed throughout the coal cake. In order to improve the strength of the coal cake, it is necessary to make the fiber length 1.0 mm or more. In terms of improving the strength of the coal cake, the longer the fibers are, the more preferable it is, and the length of the fibers mixed into the coal cake raw material is preferably 3.0 mm or more, and more preferably 5.0 mm or more. On the other hand, even if the fibers are made longer than 200 mm, the strength of the coal cake is saturated, but there is a problem that the mixability with the powdered coal cake raw material is deteriorated. Therefore, the length of the fibers mixed into the coal cake raw material is 200 mm or less, preferably 180 mm or less, and more preferably 160 mm or less.
[0028] The length of the fibers does not need to be uniform, and may be irregular. It is sufficient that a predetermined amount of fibers having a length of 1.0 mm or more and 200 mm or less are mixed. Fibers having a length of less than 1.0 mm do not contribute to improving the strength of the coal cake, but they do not reduce the strength, so there is no problem even if fine fibers are included. Fibers having a length of 200 mm or more do not reduce the strength if they are mixed in a small amount, but the strength may decrease if the amount increases. Therefore, it is desirable not to intentionally mix fibers having a length of 200 mm or more. In addition, it is considered that fibers having a shape that is thick and short, that is, fibers closer to a spherical shape, are less likely to cause the phenomenon of mutual entanglement as described above when mixed into the coal cake. As shown in the examples described later, even if thick and short fibers are used, the strength of the coal cake is not improved, but the strength is not reduced, so there is no problem even if thick and short fibers are included. What is necessary here is to mix fibers having an elongated shape, and it is preferable that the ratio of the length to the diameter of the fibers is larger. In the present invention, the ratio of length to diameter of the fibers is 10 or more, preferably 15 or more, and more preferably 30 or more.
[0029] When synthetic or natural fibers are cut and used, it is advantageous in that the length of the fibers can be set freely within a wide range, taking into consideration the target value of the coal cake strength set by each factory and the ease of mixing the coal cake raw material with the fibers. On the other hand, when using plant materials having a fibrous shape, it is difficult to set the length of the fibers freely, but it has an advantage in terms of reducing CO2 emissions by using biomass raw materials instead of binders derived from fossil fuels. The type and length of the above fibers can be freely determined depending on the operation goals of each factory (coal cake strength, reduction of CO2 emissions) and the capacity of the mixing equipment.
[0030] In the present invention, a high-strength coal cake can be produced by mixing the powdered coal cake raw material with fibers and stamping the mixed fiber raw material.
[0031] Regarding the blending ratio of fibers to the raw materials of the coal cake, as shown in the examples described later, the strength of the coal cake is improved as the blending ratio of fibers is higher, so there is no upper limit on the blending ratio from the viewpoint of the strength of the coal cake. However, in the present invention, a significant strength improvement effect is shown by blending and mixing a small amount of fibers with the raw materials of the coal cake. Therefore, from the purpose of preventing the collapse of the coal cake and stabilizing the operation, there is little advantage in increasing the strength of the coal cake more than necessary. Therefore, from an economical viewpoint, it is preferable that the blending ratio of fibers is 2.0 mass% or less with respect to 100 mass% of the raw materials of the coal cake. Blending fibers at a blending ratio of 2.0 mass% or less means blending so that the dry mass of the fibers is 2.0 mass% or less when the total dry mass of the raw materials (coal, coal distillate, other carbonaceous materials, etc., excluding fibers) used in the production of the coal cake is 100 mass%. The blending ratio of fibers is more preferably 1.5 mass% or less, and even more preferably 1.0 mass% or less.
[0032] On the other hand, even when the blending ratio of fibers is low, the effect of improving the coal cake strength corresponding to the blending ratio is exhibited, so the lower limit of the blending ratio is not particularly limited. However, from the viewpoint of producing a coal cake with higher strength and preventing the collapse of the coal cake, the blending ratio of fibers is preferably 0.01 mass% or more, more preferably 0.02 mass% or more, and even more preferably 0.05 mass% or more.
[0033] In addition, coal cake raw materials and plant-derived fibers generally contain a certain amount of moisture. Therefore, the moisture content of the coal cake raw materials and fibers is measured in advance, and the fiber blending ratio is calculated using the dry mass (mass excluding moisture). The moisture content of the fibers is calculated from the weight loss of the sample when heated and dried at 107°C for one hour using the air drying loss measurement method specified in JIS M 8812. Note that although this method is a moisture quantification method for coals, the moisture content of coal cake raw materials and fibers containing raw materials other than coal may also be measured using the same method.
[0034] The method of blending and mixing the fibers into the coal cake raw material is not particularly limited, and may be a mixer that is generally used to mix coal in a coke plant. In order to blend and mix the fibers into a large amount of coal cake raw material in a shorter time and increase productivity, a method of using a mixer with chopper blades such as PAM Apex Mixer (manufactured by Pacific Machinery Works, Ltd.) can also be exemplified.
[0035] When producing a coal cake from the fiber mixed raw material prepared as described above, a stamping device that compacts the fiber mixed raw material by impact of a falling weight may be used. In this case, when fibers having a length of 1.0 mm to 200 mm and a ratio of length to diameter of 10 or more are mixed, a coal cake having higher strength can be produced than when no fibers are mixed. Therefore, the coal cake is less likely to collapse, and the coke oven can be operated stably. In addition, even under operating conditions where the coal moisture is low and the coal cake is likely to collapse frequently, when the above fibers are mixed, the strength of the coal cake can be maintained within a range that does not cause operational problems. The effect of mixing fibers on the strength of the coal cake will be explained in more detail in the following examples.
[0036] (Metallurgical coke manufacturing method) Next, a method for producing metallurgical coke according to the present invention will be described. The method for producing metallurgical coke according to the present invention is characterized in that the coal cake produced by the above-mentioned method for producing coal cake according to the present invention is carbonized in a coke oven.
[0037] The coal cake produced by the above-mentioned method for producing a coal cake according to the present invention is mechanically charged from the side of the coke oven carbonization chamber. At this time, the coal cake is subjected to the impact of its own weight and the vibration of the charging machine. If the strength of the coal cake is low, an operational problem may occur in which the coal cake collapses during charging. In the method for producing a coal cake according to the present invention, fibers are used as a binder, which improves the strength of the coal cake and suppresses the collapse of the coal cake.
[0038] There are no particular restrictions on the conditions for carbonizing the coal cake. The coal cake can be carbonized at a temperature of about 900°C or higher using a general stamp charge coke oven.
[0039] (Strength improving material for coal cake) Next, the strength improving material for coal cake according to the present invention will be described. The strength improving material for coal cake according to the present invention is a strength improving material for coal cake used in stamp charge type coke ovens, and is characterized in that it is a fiber having a length of 1.0 mm or more and 200 mm or less.
[0040] The above-mentioned fibers may be the fibers used in the above-mentioned method for producing a coal cake according to the present invention. The requirements for the fibers may be the same as those for the fibers used in the method for producing a coal cake.
[0041] As described above, a high-strength coal cake can be manufactured by blending and mixing the fibers having a length of 1.0 mm or more and 200 mm or less as a binder into the raw material of the coal cake and stamping the obtained fiber mixed raw material. As a result, when the obtained coal cake is carbonized in a coke oven to produce coke, the collapse of the coal cake can be suppressed, and the operation of the coke oven can be stably performed. EXAMPLES
[0042] Hereinafter, examples of the present invention will be described, however, the present invention is not limited to the following examples and can be modified as desired without departing from the gist of the present invention.
[0043] Example 1 In Example 1, polyethylene fibers and polypropylene fibers having different fiber lengths and diameters were mixed with raw materials for coal cake, and a coal cake was produced by the coal cake producing method according to the present invention, and its strength was evaluated.
[0044] As the coal cake raw material, a blended coal prepared by blending raw coal so that the weighted average of the coal rank (Ro) was 0.94 was pulverized to a particle size of -3 mm (90 mass%) and used. Polyethylene fibers or polypropylene fibers were cut to the length shown in Table 1 and mixed with the above coal cake raw material at the blending ratio shown in Table 1. The moisture content of the above mixture was measured, and a calculated amount of water was added so that the moisture content was 10 mass%, which is a general condition for stamp charge coke ovens.
[0045] [Table 1]
[0046] The fiber mixture was prepared by adjusting the moisture content as described above, and the following procedure was used to prepare a coal cake. First, about 200 g of the fiber mixture was charged into a metal mold with an inner diameter of 10 cm and a height of 20 cm, and a rammer with a mass of 9 kg was dropped 10 times from a height of 30 cm from the surface of the sample, thereby compacting the charged fiber mixture by the impact. The above procedure from charging the coal to dropping the rammer was repeated 10 times to produce a coal cake with a diameter of 10 cm, a height of 20 cm, and a weight of about 2 kg. The mold was then gently removed from the coal cake, and the strength of the coal cake was measured. The strength of the coal cake was evaluated by the uniaxial compressive strength specified in JISA 1216. The results are shown in Table 1.
[0047] Table 1 shows the strength of coal cake when the coal cake raw material is mixed with synthetic fibers of different lengths and diameters. The coal cake strength (uniaxial compressive strength) varies greatly depending on the type and particle size of the coal cake raw material used. Therefore, when evaluating the effect of additives on the coal cake strength, it is best to evaluate each coal cake raw material in terms of the strength ratio to the standard, which is the uniaxial compressive strength of coal cake produced under conditions of a moisture content of 10 mass% and no additives, which are general conditions in stamp charge coke ovens.
[0048] If the strength ratio is less than 1.0, the strength of the coal cake is lower than that under general operating conditions, and it can be considered that the conditions are prone to problems such as the collapse of the coal cake. On the other hand, if the strength ratio is more than 1.0, the strength of the coal cake is higher than that under general operating conditions, and it can be considered that the conditions are desirable for stable operation in which the collapse of the coal cake is unlikely to occur. From this perspective, in the comparative example in which polypropylene fibers with a diameter of 1.2 mm are cut to a length of 5 mm or 10 mm and mixed, the strength ratio to the standard is less than 1.0, and it can be said that the strength of the coal cake is lowered by mixing the fibers, and the collapse of the coal cake is likely to occur. The reason for this is considered to be that under the conditions of the comparative example, the shape of the additive is close to a sphere, and a network in which the fibers are entangled with each other is not formed, and the effect of improving the strength of the coal cake is not observed.
[0049] On the other hand, in other examples of the present invention, the strength of the coal cake is improved by mixing fibers, making the coal cake less likely to collapse, which is a desirable condition for stable operation. From the results of this example, it is clear that the strength of the coal cake can be improved by mixing fibers having a length of 1.0 mm or more and 200 mm or less and a ratio of length to diameter of 10 or more into the coal cake raw material.
[0050] Example 2 In Example 2, the effect of mixing fibers on the strength of the coal cake was investigated under conditions in which the moisture content of the coal cake raw material was 7 mass%, which is lower than the general stamp charge operating conditions in which the moisture content was 10 mass%. To this end, a coal cake was manufactured by the manufacturing method of the coal cake according to the present invention, and its strength was evaluated.
[0051] As the coal cake raw material, a blended coal in which the weighted average of the coal rank (Ro) was 0.94 was used, which was pulverized to a particle size of -3 mm (90 mass%). Polyethylene fibers or polypropylene fibers were cut to the length shown in Table 2 and mixed with the above coal cake raw material at the blending ratio shown in Table 2. The moisture content of the above mixture was measured, and a calculated amount of water was added so that the moisture value was 10 mass%, which is a general condition in a stamp charge coke oven, or 7 mass%, which is a condition with a lower moisture content than usual. Using the coal cake raw material in which the moisture content was adjusted by mixing fibers in the above-mentioned procedure, a coal cake was produced in the same manner as in Example 1, and its strength was measured. The obtained results are shown in Table 2.
[0052] [Table 2]
[0053] Table 2 shows the effect of blending fibers on the strength of the coal cake when the moisture content of the coal cake raw material is lower than that of the general conditions in a stamp charge coke oven. As shown as a reference example in Table 2, when the moisture content of the coal cake raw material is reduced from 10% by mass to 7% by mass, the strength ratio of the coal cake to the standard falls to 0.46. Under these conditions, the coal cake frequently collapses, making it difficult to produce coke stably. As a comparative example, the strength of the coal cake when polypropylene fibers with a diameter of 1.2 mm and a length of 10 mm are blended is shown, and the strength of the coal cake is lower than that when no fibers are blended. On the other hand, in the example of the invention, by blending fibers having a length of 1.0 mm or more and a length to diameter ratio of 10 or more, it can be seen that the strength ratio is higher than the standard even under the condition that the moisture content of the coal cake raw material is 7% by mass. In other words, the moisture content of the coal cake can be reduced while maintaining the strength of the coal cake by blending fibers, thereby improving the productivity of the coke.
[0054] Example 3 As Example 3, fibers obtained from palm bunches (EFB fibers) were mixed with coal cake raw materials, and a coal cake was produced by the coal cake producing method according to the present invention, and the strength was evaluated.
[0055] For the coal cake raw material, a blended coal in which the weighted average of the coal rank (Ro) was blended to 0.93 was crushed to a particle size of -3 mm (90 mass%) and used. EFB fiber was blended and mixed with the above coal cake raw material at the blending ratio shown in Table 3. The diameter of the EFB fiber used was uniform at 0.8 mm, but the length was irregular between 50 and 100 mm. Therefore, the fiber length and the ratio of length to diameter are given a range. The moisture content of the above mixture was measured, and a calculated amount of water was added so that the moisture content was 10 mass%, which is a general condition for stamp charge coke ovens. A coal cake was manufactured in the same manner as in Example 1 using the coal cake raw material in which the EFB fiber was mixed and the moisture was adjusted by the above procedure, and the strength of the obtained coal cake was measured. The obtained results are shown in Table 3.
[0056] [Table 3]
[0057] As shown in Table 3, the strength of the coal cake can also be improved by mixing fibrous plant materials such as EFB fiber, and fibrous plant materials can be used as clean binders for stamp charge coke ovens, replacing fossil fuel-derived binders. [Industrial Applicability]
[0058] According to the present invention, the strength of the coal cake can be improved without using a caking binder.
Claims
1. A method for producing a coal cake in a stamp charge coke oven, comprising the steps of: A method for producing a coal cake, comprising: blending and mixing fibers having a length of 1.0 mm or more and 200 mm or less and a length-to-diameter ratio of 10 or more with a powdered coal cake raw material; and stamping the resulting fiber mixture raw material to obtain a coal cake.
2. The method for producing a coal cake according to claim 1 , wherein a blending ratio of the fiber is 2.0 mass% or less with respect to 100 mass% of the raw materials of the coal cake.
3. A method for producing metallurgical coke, comprising carbonizing the coal cake produced by the method according to claim 1 or 2 in a coke oven to obtain coke.
4. A strength improving material for coal cake used in a stamp charge type coke oven, characterized in that the material has a length of 1.0 mm or more and 200 mm or less, a length to diameter ratio of 10 or more, and is a fiber that is blended into the raw material of the powdered coal cake.
Citation Information
Patent Citations
Method of charging to coke oven battery
JP1976111801A
Production of metallurgical coke
JP1981026979A
Production of formed coke
JP1994172756A
Method for manufacturing coke for use in metallurgy
JP2008050516A
Method for preheated stamp charging of coal
JP1995109467A